Laser-matter interaction for radiation and energy - Malik, Hitendra K. (Boca Raton, FL : CRC Press, 2021)
The interaction of high-power lasers with matter can generate Terahertz radiations that efficiently contribute to THz Time-Domain Spectroscopy and also would replace X-rays in medical and security applications. When a short intense laser pulse ionizes a gas, it may produce new frequencies even in VUV to XUV domain. The duration of XUV pulses can be confined down to the isolated attosecond pulse levels, required to study the electronic re-arrangement and ultrafast processes. Another important aspect of laser-matter interaction is the laser thermonuclear fusion control where accelerated particles also find an efficient use. This book provides comprehensive coverage of the most essential topics, including Electromagnetic waves and lasers THz radiation using semiconducting materials / nanostructures / gases / plasmas Surface plasmon resonance THz radiation detection Particle acceleration technologies X-ray lasers High harmonics and attosecond lasers Laser based techniques of thermonuclear fusion Controlled fusion devices including NIF and ITER The book comprises of 11 chapters and every chapter starts with a lucid introduction to the main topic. Then sub-topics are sedulously discussed keeping in mind their basics, methodology, state-of-the-art and future perspective that will prove to be salutary for readers. High quality solved examples are appended to the chapters for their deep understanding and relevant applications. In view of the nature of the topics and their level of discussion, this book is expected to have pre-eminent potential for researchers along with postgraduate and undergraduate students all over the world.
OCLC-licensed vendor bibliographic record.
Keywords: Laser beams; Radiation; SCIENCE / Physics; TECHNOLOGY / Lasers; SCIENCE / Nuclear Physics